Surface Acoustic Devices: UV Direct Write Metal Enhanced Redox (MER) Domain Engineering for Realization of Surface Acoustic Devices on Lithium Niobate (Adv. Mater. Interfaces 4/2014). Issue 4 (July 2014) - Yudistira, Didit; Boes, Andreas; Rezk, Amgad R.; Yeo, Leslie Y.; Friend, James R.; Mitchell, Arnan
<x xml:space="preserve">Abstract</x> In article 1400006, D. Yudistira and co‐workers introduce a new and highly versatile domain patterning method, ultraviolet direct write Metal Enhanced Redox (UV direct write MER), that achieves deep domains with practically no thermally induced damage on the surface of lithium niobate crystals. Such a technique enables the fabrication of practical piezoelectric acoustic superlattice structures on 128° YX‐cut LiNbO3, the most widely used crystal cut for surface acoustic wave applications. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>